Is perceived value enough to create loyalty for m-wallets? Exploring the role of trust and satisfaction - Amol S. Dhaigude; Archit Vinod Tapar; Mohammad Shameem Jawed; Giridhar B Kamath (Cogent Business & Management, 2023)
This study explores the role of perceived customer value and loyalty relationships in mobile wallet (M-wallet). The study further investigates trust and satisfaction as drivers of loyalty and examines the role of trust in the traditional value-satisfaction-loyalty relationship. A total of 214 responses from M-wallet users were captured using a structured questionnaire in a cross-sectional survey design. The data collected was analyzed with the help of structural equation modeling. Trust and satisfaction in M-wallet are both found to be mediating the perceived customer value and loyalty relationship. Furthermore, results also confirm the sequential mediation impact of trust and satisfaction between the perceived customer value and loyalty relationship. The findings help practitioners in tailoring their customer relationship strategies to promote M-wallet loyalty. Finally, this study recommends that managers should emphasize leveraging trust and satisfaction to shape loyalty in addition to customer value. They should focus on initiatives to win trust, satisfy the customers, and enhance long-term customer relationships.
Keywords: 650; internet commerce; loyalty; mobile wallet; online payment; perceived value; satisfaction; serial mediation; trust